Roundness and matt degree of quartz grain surfaces in (fluvio-)glacial deposits of the Pomeranian Stage (Weichselian) in northeast Germany - Górska-Zabielska, Maria (Geologos, 2015)
Glacial tills and fluvioglacial sediments deposited by the ice-sheet during the Pomeranian Stage (Weichselian) in northeast Germany have been examined in terms of the degree of abrasion, rounding and frosting of quartz grain surfaces in order to determine the conditions and processes that occurred in the alimentation environment of the fine-grained material, as well as during transport. Strata in the glaciomarginal zone and the hinterland of the Pomeranian Stage in the area represent diverse lithofacies, but have similar textural features. These features illustrate mainly that a high-energy aquatic environment had reacted with glacial deposits prior to their inclusion into the ice mass and deposited in the area covered by the Odra lobe. The lack of regional diversification in the character of quartz grain surfaces in glacial deposits between the German part of the Odra lobe and the remainder of the area analysed is recorded solely in the morphological dimension, i.e. the outlet fragment of the ice-front’s course, but not in textural features of the sediments